The Impact of Love of Money and Islamic Financial Literacy on Muslims' Financial Self-Management in East Java - Lusianah Dhewi Findartika; Elfira Maya Adiba (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the influence of Islamic financial literacy and the love of money on Muslims' personal financial management in East Java, both directly and through the mediation of financial self-efficacy. The study used a quantitative approach, employing a survey of Muslims from Generations Y and Z in East Java, selected through purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that Islamic financial literacy and love of money have a significant positive effect on personal financial management and financial self-efficacy. Financial self-efficacy was shown to have the strongest influence on personal financial management and acts as a partial mediator in the relationship between Islamic financial literacy and love of money with personal financial management. In conclusion, improving Muslim personal financial management requires not only strengthening Islamic financial literacy but also building financial self-confidence. Therefore, an effective Islamic financial literacy program needs to integrate cognitive and psychological aspects simultaneously.